Self-care that cancer patients receiving outpatient radiation therapy should practice - Hiasa, Tomohiro (The Journal of Radiological Nursing Society of Japan, 2024)
The purpose of this study was to clarify the self-care that cancer patients receiving outpatient radiation therapy should practice during the treatment process. First, we created a draft 48 item self-care list that should be put into practice based on a literature review and a questionnaire survey of certified nurses. Next, the content validity of the self-care list was examined using the modified Delphi method by a total of 6 people: 3 Certified Nurse Specialists in Cancer Nursing and 3 Certified Nurses in Radiation Oncology Nursing. The examination procedure consisted of a first survey using a questionnaire, a face-to-face meeting, and a second survey using a questionnaire. As a result, 44 items were selected as representing self-care that cancer patients receiving outpatient radiation therapy should practice during the treatment process, meeting the consensus standard of I-CVI 0.78 or higher. The 44 self-care items consisted of 7 items applicable to the time of choosing treatment, 10 items covering the period from decision-making to initial irradiation, 20 items relating to the treatment period, and 7 items concerning the period after treatment. The created 44 item self-care list can be used as nursing indicators to support self-care, and help improve patients’ self-care.